Pengolahan Limbah Kulit Buah menjadi Eco-Enzyme pada Siswa SMKN 10 Merangin - Viza, Rivo Yulse; Sisca, Vivi; Handayani, Pitri; Ratih, Arista (LPPM Universitas Bumigora, 2023)
Fruit peel waste, so that it is not problematic for the environment and health, can be used as a source of eco enzyme raw materials, which are the result of fermentation of fruit/vegetable residue, sugar, and water. Eco enzymes can be made by mixing organic waste, such as fruit and vegetable waste, with sugar and water in a ratio of 3: 1: 10. Basically, all fruit and vegetable waste can be used as raw material for making eco enzymes. The service activity of processing fruit peel waste into Eco-enzyme invites students to handle waste in a simple way around the school. This service activity is carried out through group practice. Making eco enzyme invites students to use this liquid as a natural cleanser, one of the experiments to handle the waste. Using fruit peel waste as an eco enzyme as an alternative to cleaning fluid adds insight and skills in processing fruit peel waste into cleaning fluid.